The Female FTSE Report 2005: New look women directors add value to FTSE 100 Boards - Singh, Val; Vinnicombe, Susan (Cranfield University, 2005)
Seventy-eight FTSE 100 companies, a new record number, now have women directors, up 13% from last year. But the breakthrough is in who these new female directors are and the diverse experiences they bring to the boardroom. The new female directors are more likely to be international, have board experience and have much richer, more varied work backgrounds than the men. Six FTSE 100 companies appointed their first ever woman director (Intercontinental Hotels, Capita, ITV, BHP Billiton, Rio Tinto, Sage). However, only eleven FTSE 100 companies now have female executive directors, down from 13 in 2005 and worryingly, below the 2002 figure. Still 22 of the FTSE 100 boards are all-male, an anachronism in 2005.